A comparative study of shoulder replacement outcomes using linked national registry and hospital data from England and Denmark - Epaminondas Markos Valsamis; Josefine Beck Larsen; Theis M. Thillemann; Stephen E. Gwilym; Gary S. Collins; Inger Mechlenburg; Jonathan L. Rees (BMC Medicine)
Abstract Background The incidence of shoulder replacement surgery continues to rise internationally. The aim of this study was to compare revision surgery, reoperations and serious adverse events after shoulder replacement surgery in England and Denmark. Methods Linked National Joint Registry and NHS Hospital Episode Statistics of England, and linked Danish Shoulder Arthroplasty Registry and Danish National Patient Registry data were available from 1 April 2012 to 31 December 2020. All primary shoulder replacements in adult patients were included. Revision surgery, reoperations and serious adverse events were compared between the two countries, and stratified by procedure type and surgical indication. The risk of revision and serious adverse events were adjusted for age, sex and comorbidities, using flexible parametric survival models and logistic regression models, respectively. Results A total of 41,471 and 9,268 primary shoulder replacement procedures were analysed from England and Denmark, respectively. The mean patient age in Denmark was 70.6 years (SD 10.1) and in England 72.6 years (SD 9.9). Danish patients had a lower risk of serious adverse events (4.5%) compared to patients in England (5.6%), but a slightly higher risk of re-operations by 1 year (Denmark 2.3% [95% CI 2.0% to 2.6%], England 1.7% [95% CI 1.6% to 1.8%]). There was a slightly lower risk of revision joint replacement surgery by 8 years in Denmark (5.1% [95% CI 4.5% to 5.8%]) compared to England (5.7% [95% CI 5.4% to 6.1%]). The reverse total shoulder replacement had a higher revision rate in Denmark, but the anatomical total shoulder replacement and humeral hemiarthroplasty had lower revision rates. Denmark had a considerably higher revision rate for patients having surgery for acute trauma. These results remained the same after adjusting for age, sex, and the Charlson Comorbidity Index. Conclusions While there was variation in the demographics of patients having shoulder replacement surgery in England and Denmark, differences in serious adverse events and revision rates were observed despite case-mix adjustment. Some of this variation might be attributed to the differences seen in the use of different procedures for different surgical indications between the two countries.